Divine vs. Human Law: The Quarrel between the Anti- and Pro-Constitutionalist Jurists in Iranian Constitutional Revolution of 1906 - Mirabian Tabar, Mehdi (Religions, 2021)
This study investigated the quarrel between the pro-and anti-constitutionalist jurists following the establishment of the first National Consultative Assembly (Majlis) in Iran and the drafting of the first constitution in 1906. A group of shi῾ite jurists launched an attack on Majlis, in addition to the ideas of human legislation, freedom, and equality, by considering the Islamic Sharī῾a law to be a set of perfect and impeccable laws. In response to these oppositions, the pro-constitutional jurists argued in favor of the constitutional movement. In this paper, it is argued that the quarrel could be considered as evidence for the perennial tension between the divine and human law in Islam. It appears that examining this conflict may shed light on incidents shaping the history of contemporary Iran.